menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
When using substitution to solve this system of equations, what is the result of the first step? x = 6 y + 3 x + 2 y = 5 A. x + 2 ( 6 x + 3 ) = 5 C. 6 y + 3 + 2 y = 5 B. x + 2 ( 6 y + 3 ) = 5 D. 6 x +
asked
Sep 27, 2021
41.0k
views
0
votes
When using substitution to solve this system of equations, what is the result of the first step?
x
=
6
y
+
3
x
+
2
y
=
5
A.
x
+
2
(
6
x
+
3
)
=
5
C.
6
y
+
3
+
2
y
=
5
B.
x
+
2
(
6
y
+
3
)
=
5
D.
6
x
+
3
+
2
x
=
5
Mathematics
high-school
Janine Rawnsley
asked
by
Janine Rawnsley
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
Answer:
answer
Explanation:
one of you answer this question
Hxin
answered
Oct 3, 2021
by
Hxin
5.3k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.6m
questions
7.3m
answers
Other Questions
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
(3x1,000,000)+(3x100,000)+(2x100) what is this number written in standard form?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org